Bedingungen der Wissensproduktion. Qualifizierung, Selbstoptimierung und Prekarisierung in Wissenschaft und Hochschule
Angesichts der aktuellen Arbeitsbedingungen in Wissenschaft und Hochschule – zwischen Qualifizierung, Selbstoptimierung und Prekarisierung – hangeln sich Wissenschaftler*innen jenseits unbefristeter Professuren von einem befristeten Arbeitsvertrag zum nächsten. Unter prekarisierten Arbeitsbedingungen stemmen sie einen Großteil der wissenschaftlichen Arbeit in Forschung und Lehre. Der Band diskutiert diese Verhältnisse der Wissensproduktion aus theoretischen, historischen, politischen wie empirischen Blickrichtungen, wobei der Fokus der Analysen über ungleichheitstheoretische erziehungs- und sozialwissenschaftliche Perspektivierungen sowie solche angrenzender disziplinärer Felder grundiert ist. Er leistet damit auch einen Beitrag zu den Bestrebungen, für bessere Arbeitsbedingungen an Hochschulen und in der Wissenschaft einzutreten.

Bedingungen der Wissensproduktion an Hochschulen und die Notwendigkeit ihrer disziplinären Bearbeitung - Leinfellner, Stefanie; Thole, Friederike; Sehmer, Julian; Simon, Stephanie (Bedingungen der Wissensproduktion. Qualifizierung, Selbstoptimierung und Prekarisierung in Wissenschaft und Hochschule)

Biographien in der Wissenschaft zwischen Qualifizierung, (Selbst-)Optimierung und Prekarisierung - Simon, Stephanie; Sehmer, Julian; Thole, Friederike; Leinfellner, Stefanie (Bedingungen der Wissensproduktion. Qualifizierung, Selbstoptimierung und Prekarisierung in Wissenschaft und Hochschule)

Asymptotics for the infinite Brownian loop on noncompact symmetric spaces - Papageorgiou, Efthymia (Journal of Elliptic and Parabolic Equations)
Abstract The infinite Brownian loop on a Riemannian manifold is the limit in distribution of the Brownian bridge of length T around a fixed origin when $$T → +∞ $$ T → + ∞ . The aim of this note is to study its long-time asymptotics on Riemannian symmetric spaces G / K of noncompact type and of general rank. This amounts to the behavior of solutions to the heat equation subject to the Doob transform induced by the ground spherical function. Unlike the standard Brownian motion, we observe in this case phenomena which are similar to the Euclidean setting, namely $$L^1$$ L 1 asymptotic convergence without requiring bi- K -invariance for initial data, and strong $$L^{∞ }$$ L ∞ convergence.
Keywords: Applied Mathematics; Numerical Analysis; Analysis

Scheduling Periodic Segmented Self-Suspending Tasks without Timing Anomalies - Lin, Ching-Chi; Günzel, Mario; Shi, Junjie; Seidl, Tristan Taylan; Chen, Kuan-Hsun; Chen, Jian-Jia (2023 IEEE 29th Real-Time and Embedded Technology and Applications Symposium (RTAS))

Simulation Environment with Customized RISC-V Instructions for Logic-in-Memory Architectures

Probabilistic Reaction Time Analysis - Günzel, Mario; Ueter, Niklas; Chen, Kuan-Hsun; von der Brüggen, Georg; Chen, Jian-Jia (ACM Transactions on Embedded Computing Systems)
In many embedded systems, for instance, in the automotive, avionic, or robotics domain, critical functionalities are implemented via chains of communicating recurrent tasks. To ensure safety and correctness of such systems, guarantees on the reaction time, that is, the delay between a cause (e.g., an external activity or reading of a sensor) and the corresponding effect, must be provided. Current approaches focus on the maximum reaction time, considering the worst-case system behavior. However, in many scenarios, probabilistic guarantees on the reaction time are sufficient. That is, it is sufficient to provide a guarantee that the reaction does not exceed a certain threshold with (at least) a certain probability. This work provides such probabilistic guarantees on the reaction time, considering two types of randomness: response time randomness and failure probabilities. To the best of our knowledge, this is the first work that defines and analyzes probabilistic reaction time for cause-effect chains based on sporadic tasks.

Probabilistic Reaction Time Analysis - Günzel, Mario; Ueter, Niklas; Chen, Kuan-Hsun; von der Brüggen, Georg; Chen, Jian-Jia (ACM Transactions on Embedded Computing Systems)
In many embedded systems, for instance, in the automotive, avionic, or robotics domain, critical functionalities are implemented via chains of communicating recurrent tasks. To ensure safety and correctness of such systems, guarantees on the reaction time, that is, the delay between a cause (e.g., an external activity or reading of a sensor) and the corresponding effect, must be provided. Current approaches focus on the maximum reaction time, considering the worst-case system behavior. However, in many scenarios, probabilistic guarantees on the reaction time are sufficient. That is, it is sufficient to provide a guarantee that the reaction does not exceed a certain threshold with (at least) a certain probability. This work provides such probabilistic guarantees on the reaction time, considering two types of randomness: response time randomness and failure probabilities. To the best of our knowledge, this is the first work that defines and analyzes probabilistic reaction time for cause-effect chains based on sporadic tasks.

Guest Editorial: Special Issue on Systems Optimizations for DSP and AI Applications - Chen, Kuan-Hsun; Lin, Yung-Chia; Lee, Jenq-Kuen (Journal of Signal Processing Systems)

Rapid NVM Simulation and Analysis on Single Bit Granularity Featuring Gem5 and NVMain - Hölscher, Nils; Truong, Minh Duy; Hakert, Christian; Seidl, Tristan; Chen, Kuan-Hsun; Chen, Jian-Jia (2023 IEEE 12th Non-Volatile Memory Systems and Applications Symposium (NVMSA))

Timing-Aware ROS 2 Architecture and System Optimization - Teper, Harun; Betz, Tobias; Von Der Brüggen, Georg; Chen, Kuan-Hsun; Betz, Johannes; Chen, Jian-Jia (2023 IEEE 29th International Conference on Embedded and Real-Time Computing Systems and Applications (RTCSA))

Buildings, valuated matroids, and tropical linear spaces - Battistella, Luca; Kühn, Kevin; Kuhrs, Arne; Ulirsch, Martin; Vargas, Alejandro (Journal of the London Mathematical Society)
Abstract Affine Bruhat–Tits buildings are geometric spaces extracting the combinatorics of algebraic groups. The building of parameterizes flags of subspaces/lattices in or, equivalently, norms on a fixed finite‐dimensional vector space, up to homothety. It has first been studied by Goldman and Iwahori as a piecewise‐linear analogue of symmetric spaces. The space of seminorms compactifies the space of norms and admits a natural surjective restriction map from the Berkovich analytification of projective space that factors the natural tropicalization map. Inspired by Payne's result that the analytification is the limit of all tropicalizations, we show that the space of seminorms is the limit of all tropicalized linear embeddings and prove a faithful tropicalization result for compactified linear spaces. The space of seminorms is in fact the tropical linear space associated to the universal realizable valuated matroid.

Du Val Singularities - Burban, Igor (Springer Proceedings in Mathematics & Statistics)

Du Val Singularities - Burban, Igor (Springer Proceedings in Mathematics & Statistics)

Privacy in the Age of Neurotechnology: Investigating Public Attitudes towards Brain Data Collection and Use - Kablo, Emiram; Arias Cabarcos, Patricia (Proceedings of the 2023 ACM SIGSAC Conference on Computer and Communications Security)

Overcoming Theory: Designing Brainwave Authentication for the Real World - Röse, Markus; Kablo, Emiram; Arias Cabarcos, Patricia (Proceedings of the 2023 European Symposium on Usable Security)

Biopolitik und Biopoethik: Modi der Aushandlung menschlichen Lebens in (Gegenwarts-)Literatur, Film und Serie - Hannebohm, Ronja (Biopolitik(en) in Literatur, Film und Serie: Aushandlungs- und Reflexionsräume vom 18. Jahrhundert bis heute)

Biopolitik(en) in Literatur, Film und Serie: Aushandlungs- und Reflexionsräume vom 18. Jahrhundert bis heute

Implementierungsstrategien einer Berufsbildung für nachhaltige Entwicklung im Berufsfeld Ernährung und Hauswirtschaft am Beispiel der curricularen Verankerung eines Bildungsplans aus NRW - Loy, Sarah (FÜR NACHHALTIGKEIT SORGEN - DOKUMENTATION DER JAHRESTAGUNG 2023 DER DEUTSCHEN GESELLSCHAFT FÜR HAUSWIRTSCHAFT)

Ergebnisse qualitativer Praxisforschung zur inklusiven Schulentwicklung nutzen - Impulse aus dem Projekt Wohlbefinden und Inklusion an der Laborschule Bielefeld (WILS) für kollegiumsinterne Fortbildung - Geist, Sabine; Külker, Anna; Dorniak, Marlena; Siepmann, Christof; Uffmann, Gunnar; Zentarra, Dominik; Kullmann, Harry (Jahrbuch Laborschulforschung 2023)
Seit 1974, also mit Beginn der Schulgründung, versteht sich die Laborschule als eine „Schule für alle“, als „Gesellschaft im Kleinen“. Ihrem Anspruch entsprechend sollte niemand prinzipiell vom Besuch der Schule ausgeschlossen werden. Eine Orientierung an den Idealen einer inklusiven Schule war damit von Beginn an gegeben (vgl. u.a. Demmer-Dieckmann & Struck, 2001; Begalke, Clever, Demmer-Dieckmann & Siepmann, 2011; Thurn, 2017). Die Laborschule will den Kindern und Jugendlichen Lebens- und Erfahrungsraum und Gesellschaft im Kleinen sein, ein Ort, an dem „Heranwachsende im täglichen Leben die Tugenden mündiger Bürgerinnen und Bürger lernen können“ (Thurn & Tillmann 2011, 10). Zugleich ist die Schule als erste Universitätsschule Deutschlands und Versuchsschule des Landes Nordrhein-Westfalen seit 50 Jahren ein „Laboratorium“ für die Erziehungswissenschaft, und bis heute soll sie, neben einigen anderen Aufgaben, „Probleme im pädagogischen Alltag aufspüren, sich neuen pädagogischen Herausforderungen stellen und [...] vorzeigbare Konzept entwickeln und erproben“ (Thurn & Tillmann 2011, 14). Genau für diese Aufgabe arbeiten Lehrkräfte neben ihrer Lehrtätigkeit zugleich als Forschende an Themen der Praxis. Sie tun dies gemeinsam mit den universitären Mitarbeiter*innen der Wissenschaftlichen Einrichtung Laborschule und ggf. weiteren Wissenschaftler*innen (s.u.) als gleichberechtigte Partner*innen. Über viele Jahre hinweg hat ein multiprofessionelles Team aus schulischen und universitären Kolleg*innen der Schul- und Sonderpädagogik in dem Forschungs- und Entwicklungsprojekt (FEP) „Wohlbefinden und Inklusion an der Laborschule (WILS)“ gemeinsam gearbeitet und gewonnene Erkenntnisse publiziert (vgl. Kullmann, Geist & Lütje-Klose, 2015; Külker, Dorniak, Geist, Kullmann, Lutter, Lütje-Klose & Siepmann, 2017; Geist, Kullmann, Lütje-Klose & Siepmann, 2019; Goldan, Kullmann, Zentarra, Geist & Lütje-Klose, 2021 und ganz aktuell Külker et al. sowie Kullmann et al. in diesem Band). Zentrales Anliegen dieses Beitrages ist es, darzustellen, wie im Rahmen dieses Forschungs- und Entwicklungsprojektes Forschungsergebnisse für die Laborschule nutzbar gemacht wurden. Diese dem Anspruch des Lehrer*innenforschermodells folgende Aufgabe stellte sich die Forschungsgruppe in der letzten Phase des Forschungsprojektes explizit. Der Transfer der Forschungsergebnisse in die Schule ist daher das zentrale Thema des vorliegenden Beitrags. Dabei wird vor allem auf die Forschungsergebnisse von Külker et al. (in diesem Band) Bezug genommen. Wir arbeiten zudem heraus, welche Möglichkeiten in einer dicht an schulischen Praxisproblemen befindlichen Schulentwicklungsarbeit liegen. Diese allgemeinen Erkenntnisse zur Schulentwicklungsarbeit lassen sich auch für die Schulentwicklungsarbeit in Regelschulen nutzen.
Keywords: Schul- und Unterrichtsentwicklung; Inklusion; Praxisforschung; Schulinterne Fortbildung